A comparative study on international marketing mix in China and India: The case of McDonald's - Chan, S. Yeu; Leong, Kong C.; Tong, Lee C.; Hang, Su; Tang, Y.; Abdul Ghani, Ahmad Bashawir; Subhan, Muhammad (Elsevier Ltd., 2012)
This study examines the international marketing mix done by the McDonald’s in two different important markets.The objective is to analyze and understand the similarities and differences of the international marketing mix strategy implementation by the company.Using comparative analysis, this study focused on 4P approach of marketing mix which is based on product, price, promotion and place analysis.McDonald’s marketing strategy in China and India were used for this study.The study found that the McDonald’s has adopted different kind of its 4P in their international marketing mix based on both, localization and globalization approaches.